Beef tallow: Extraction, physicochemical property, fatty acid composition, antioxidant activity, and formulation of lotion bars - Chutima Limmatvapirat, Sontaya Limmatvapirat, Wantanwa Krongrawa, Juthaporn Ponphaiboon, Thanatcha Witchuchai, Pannawich Jiranuruxwong, Phuwarin Theppitakpong, Pavisanat Pathomcharoensukchai (Journal of Applied Pharmaceutical Science, 2021)
The objective of this study was to transform beef adipose tissues into tallow for the production of lotion bars. This study managed to evaluate the influence of various rendering methods on the yields, physicochemical properties, fatty acid composition, and antioxidant activities of tallow. All obtained tallow samples were found to possess saponification values, acid values, peroxide values, refractive indexes, heavy metal contents, and microbial contamination within the acceptable limits. The results also revealed that the low-temperature (LT) rendering method was the most effective method for preparation of tallow and the soft fat (SF) had a higher unsaturated fatty acid content and stronger antioxidant activity than hard fat. Due to the highest content of unsaturated fatty acids and antioxidant activity of tallow prepared from SF extracted with the LT rendering method, it was used as an active ingredient in lotion bars. The optimized lotion bars were characterized by hardness, homogeneity, color, microbial loads, and heavy metal contents. The nongreasy lotion bar containing 40% w/w beef tallow was proved to be stable under heating-cooling cycle stability testing. Thus, qualified beef tallow together with shea butter and bee wax can be utilized to produce lotion bars.
Keywords: Tallow, physicochemical property, fatty acid composition, antioxidant activity, lotion bar.